On Photocatalytic Activity of Systems of Titania/(Fe (II, III))-Type in Aqueous Suspensions - V. A. Gorbunova; L. M. Sliapniova (Наука и техника)
. The photocatalytic activity of three systems, promising for chemical water purification technologies, was experimentally compared, based on a combination of titanium dioxide/(Fe(II, III)), applying to the model oxidation reaction of methylorange organic dye in an aqueous medium. Herewith the cases of photocatalytic systems were investigated, which are based on: a) titania hydrosol obtained by hydrolysis of titanium isobutylate; b) a similar hydrosol with addition of Fe(III) ions; c) suspension of ilmenite powder based on FeTiO3. As a result of the investigation, the increase of the rate of destruction of methylorange by more than two times was found in the system with the introduction of a small amount of iron ions into initial suspension of the TiO2 hydrosol (at the obtaining a medium with the Fe3+ concentration up to 3.7 × 10–5 M). In the photocatalytic system, based on the suspension of pretreated (with suphation and calcination) ilmenite powder, enough high photocatalytic activity (the degree of methylorange decomposition up to 77 %) was measured but at a higher exposure than for the case of systems based on the TiO2 hydrosol. For the photocatalytic systems of the type being investigated, a possible mechanism of increasing their oxidative activity was briefly considered, which requires an additional physico-chemical analysis.